Nonlinear Properties of Ge-rich Si1−xGex Materials with Different Ge Concentrations. Issue 1 (December 2017) - Serna, Samuel; Vakarin, Vladyslav; Ramirez, Joan-Manel; Frigerio, Jacopo; Ballabio, Andrea; Roux, Xavier; Vivien, Laurent; Isella, Giovanni; Cassan, Eric; Dubreuil, Nicolas; Marris-Morini, Delphine
Abstract Silicon photonics is a large volume and large scale integration platform for applications from long-haul optical telecommunications to intra-chip interconnects. Extension to the mid-IR wavelength range is now largely investigated, mainly driven by absorption spectroscopy applications. Germanium (Ge) is particularly compelling as it has a broad transparency window up to 15 µm and a much higher third-order nonlinear coefficient than silicon which is very promising for the demonstration of efficient non-linear optics based active devices. Si1−x Gex alloys have been recently studied due to their ability to fine-tune the bandgap and refractive index. The material nonlinearities are very sensitive to any modification of the energy bands, so Si1−x Gex alloys are particularly interesting for nonlinear device engineering. We report on the first third order nonlinear experimental characterization of Ge-rich Si1−x Gex waveguides, with Ge concentrations x ranging from 0.7 to 0.9. The characterization performed at 1580 nm is compared with theoretical models and a discussion about the prediction of the nonlinear properties in the mid-IR is introduced. These results will provide helpful insights to assist the design of nonlinear integrated optical based devices in both the near- and mid-IR wavelength ranges.